Síntese de ferrita de zinco (ZnFe2O4) por diferentes rotas e seu uso na reação heterogênea de foto-fenton. - Anchieta, Chayene Gonçalves (2015)
In this work, zinc ferrite oxide was performed (ZnFe2O4) was synthesized by the solvothermal conventional method and the microwave-assisted solvothermal route. The influence of different synthesis as well as their variables on the physical properties of the material were investigated. The powders were characterized by X-ray diffraction (XRD), infrared spectroscopy (FTIR), nitrogen adsorption/desorption measurements by the Brunauer-Emmett-Teller method (BET), and atomic force microscopy (AFM). The produced ferrite was used as catalyst and its activity was investigated in the photo-Fenton reaction for the degradation of textile organic dye (Procion Red H-E7b) under visible light irradiation. In the experiments, different process variables such as dye and hydrogen peroxide concentrations, pH and reaction time were analyzed. The rate constants for the photo-Fenton reactions were determined for both materials prepared by different routes. The synthesis results demonstrated the formation of particles with different physical properties such as surface area, pore volume and size. The experiments of photo-Fenton reaction indicated that the materials prepared in this work present satisfactory activity for the degradation of organic pollutant, 97% de decolorization and 60% de mineralization, in aqueous solution. All studied variables of the reaction process significantly influenced on the catalytic process.